Technology on the Run: Promoting Active Behavior in Diverse Ict-Supported Physical Education Classes - Hirsh , Alon (Studia Edukacyjne, 2018)
Technology in education is defined as one that achieves a practical purpose and that can assist teachers in motivating students. In the past, instructional technology consisted of mainly visual instruction, made up of pictures, films, graphs, charts, and other visual aids. By 1985, the Internet was already well established as a technology supporting a broad community of researchers and developers. Today’s children are known as the “iGeneration” due to their advanced technology skills and use. It is estimated that teenagers spend from 15 up to 20 hours each day “multitasking”, i.e. using different forms of ICT tools. The use of technology devices turned to be an integral part of sporting performance analysis, allowing coaches and teachers to understand the physical demands on team sport athletes. The advances in ICT in the 21st century involves children that are naturally growing in areas of higher levels access to information. Nowadays, a collection of ICT tools such as pedometers, smartphones, tablets (applications), virtual reality simulators, heart rate monitors, and others, are being used in physical education to enhance engagement, pedagogy and performance. It is critical for children to adapt their capacity to acquire knowledge and develop their skills through technology usage. If these ICT tools are used properly in PE classes, they have the potential to impact teachers’ teaching practice and, consequently, student learning. Teachers should possess the skills and behaviors of digital-age professionals, particularly in physical education. Technology usage would be beneficial for increasing physical activity, improving dietary choices and encouraging other health-related behaviors.